SMART LEARNING ENVIRONMENTS AND COMMUNICATION TECHNOLOGIES - Uktamov Oybek Shuxratjon o'g'li (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Intelligent educational environments and communication technologies are an important factor in radically changing the modern educational process. The rapid technological progress in the field of Education serves to improve students 'learning patterns and improve teachers' performance. This article will analyze in detail the nature of intelligent educational environments and communication technologies, their role in the educational process, their advantages, as well as their future prospects.